Efficacy and Safety of Thermal Ablation for Treating Lymph Node Metastasis From Papillary Thyroid Carcinoma: A Systematic Review and Meta-Analysis - Ding, Zheng; Chen, Juan; Chen, Zhiguang; Zeng, Xiaoke; Zheng, Pengchao; Wang, Xuemei; Cui, Xinwu; Sang, Liang (Frontiers in Oncology, 2022)
Objective: To evaluate the efficacy and safety of thermal ablation, including radiofrequency ablation (RFA), microwave ablation (MVA), and laser ablation (LA), for treating lymph node metastasis (LNM) from papillary thyroid carcinoma (PTC). Design and Methods: PubMed and EMBASE were searched for studies reporting the efficacy and safety of thermal ablation for treating LNM in PTC. After selecting the relevant literature (including 11 papers, 208 patients, 412 lymph nodes), the QUADAS-2 tool was used to evaluate its quality. Then, both the fixed-effects and random-effects models combined with subgroup analysis were used to calculate data on volume changes in metastatic lymph nodes and changes in serum thyroglobulin (Tg) levels. We pooled the proportion of major and overall complication rates and complete disappearance rates and used subgroup forest plots and funnel plots for visual representation. Because of publication bias, we also performed a trim-and-filled model for correction. The rate of recurrence and distant metastasis with ablated details were pooled. Results: In the 11 articles (208 patients and 412 diseased lymph nodes), all thermal ablation methods showed effectiveness in reducing lymph node volume (P = 0.02) and serum Tg levels (P < 0.01) which showed no between-group difference. The pooled proportion of major complications was 0%(95% CI: -0.14; 0.15, P = 1) and the overall complication rate was 5% (95% CI: -0.09; 0.20, P = 1), which revealed no significant difference among modalities. The pooled proportion of the complete disappearance rate was 82% (95% CI: 0.43; 0.96, P < 0.01) and the data with statistical significance which contains RFA and LA showed complete disappearance rate was 59% and 81% respectively. Conclusion: All thermal ablation methods, including RFA, MWA, and LA, were effective and safe for treating LNM in PTC and were especially suitable for nonsurgical patients. Besides, subgroup analysis showed no significant difference, except for LA is better than RFA in complete disappearance rate.